ENHANCING FINANCIAL STATEMENT QUALITY : THE MODERATING EFFECT OF HUMAN RESOURCE COMPETENCY IN IMPLEMENTING FINANCIAL ACCOUNTING STANDARDS - Salisa, Naila Rizki; Ashsifa, Izza; Kuncoro, Muhammad Teguh; Prasetyaningrum, Indah Dwi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
Financial statements serve as crucial information for decision-making. Despite implementing Financial Accounting Standards (SAK) EMKM and ETAP by the Institute of Indonesian Chartered Accountants (IAI), many Micro, Small, and Medium Enterprises (MSMEs) still fail to align their financial statements with these standards. Consequently, the financial statements generated lack the necessary information and consistency, posing difficulties in making meaningful comparisons. The objective of this research is to investigate the impact of financial accounting standards implementation on the quality of financial statements, considering the moderating variable of human resource competency Data collection involved questionnaires targeting all MSMEs registered with the Manpower, Industry, Cooperatives, Small and Medium Enterprises Office in Kudus Regency (totaling 17,284 MSMEs). The research adopted a convenience sample method to collect data, and data analysis was conducted using structural equation modeling (SEM) with path analysis conducted through SMART PLS 4.0. The findings indicated a positive impact of financial accounting standards implementation on the quality of financial statements. However, human resource competency was found unable to moderate this impact. This research contributes valuable insights to MSMEs, affirming that adherence to financial accounting standards, particularly SAK EMKM and ETAP, can enhance the quality of their financial statements.